ANALISIS BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI DAN PENDIDIKAN (STUDI EMPIRIS KOTA DAN KABUPATEN DI SUMATERA BARAT) - Deviani ' (PEKBIS, 2016)
The Purpose of this research is to examine directly effect variables Local govermentExpenditure on economic growth, to examine directly effect economic growth oneducation also to examine indirectly effect Local goverment Expenditure variableson education. The samples of study are region expense budget in 2006 – 2008 at 19municipal. The result of study with regression indicate that variables Localgoverment Expenditure namely growth of capital expenditure ratio have positivesignificantly effect on economic growth, but municipal contribution ratio directly havenegatif significantly effect on economic growth, while capital expenditure ratiodirectly have not significantly effect on economic growth. Economic growth directlyhave not significantly effect on education.Keyword: Local goverment expenditure, economic growth and education